Cation coordination and hydrogen bonding in potassium and magnesium-based di-amidosil hybrids - Nunes, Sílvia (2008)
Fourier transform mid-infrared and Raman spectroscopies were employed to elucidate the cation/ alkylene chains, cation/cross-link, cation/anion interactions and hydrogen bonding occurring in amorphous di-amide cross-linked alkylene/siloxane hybrid materials (di-amidosils) doped with potassium and magnesium triflates (KCF3SO3 and Mg(CF3SO3)2, respectively). Materials with compositions oo > n > 5 (where n expresses the molar ratio of carbonyl oxygen atoms per guest cation) were investigated. The conformations (gauche) of the alkylene el-iains of the host di-amidosil matrix are not affected by the presence of the guest salt in both doped di-amidosil families. The K+ and Mg2+ ions coordinate to the carbonyl oxygen atoms of the amide cross-links within the whole range of salt concentration considered, leading to the saturation of the cross-linkages, to a redistribution of the amide-amide hydrogen-bonded aggregates of the host matrix and, in the case of the K+-doped sample with n = 10, to the formation of a new type of aggregate, stronger and more ordered than those detected at lower salt content. In both di-amidosil systems guest salt addition leads to the increase of ionic associated species and to a concomitant decrease of the concentration of "free" anions.